The associations of COVID-19 percent positivity rate, relationship quality, and season with daily anxiety and depression in couples living in NYC - Cornelius, Talea; DiGiovanni, Ana M.; Bolger, Niall (Frontiers in Psychology, 2022)
Background The COVID-19 pandemic changed nearly every aspect of daily life and had detrimental effects on mental health. Yet, impacts have been heterogeneous. We tested whether fluctuations in local COVID-19 percent positivity rates were associated with daily anxiety and depression in couples living in NYC, as well as whether these associations varied by relationship quality or season. We expected that adverse impacts of COVID-19 may be attenuated by high-quality relationships and during warmer months, or that people may habituate over time. Methods Data on seven-day rolling average COVID-19 percent positive rate each day in NYC were merged with a 14-day dyadic diary study of cohabiting couples living in NYC between August 2020 through April 2021 (232 individuals from 116 couples; mean age 28.42 years, 52.59% female, 53.02% White). Dyadic multilevel models estimated the association COVID-19 positivity rate, season (sine and cosine of the calendar date), baseline relationship quality, and all two-and three-way interactions of these variables with daily anxiety and depression. Covariates included weekend and COVID-positive case within the couple. Results Anxiety and depression mirrored COVID-19 positivity rates, and there was some evidence for habituation over time. Significant two-and three-way interactions suggested that being in a high-quality relationship buffered the association of COVID-19 positivity rate with both anxiety and depression during months when cases were low. Anxiety was elevated for individuals in high- (v. low-) quality relationships during the December–January surge. Conclusion Seven-day rolling average COVID-19 percent positivity rate was associated with daily anxiety and depression among couples living in NYC. There was some evidence that individuals habituated to this stressor over time and that high-quality relationships were protective for mental well-being; however, there was some suggestion that couples in high-quality relationships may have engaged in processes such as co-rumination during surges, worsening their daily anxiety.